The effect of marketing innovation, market orientation, and social capital on competitive advantage and marketing performance: A study in MSMEs of embroidery Central Java Province - Ag. Sunarno Handoyo (Universitas Hayam Wuruk Perbanas, 2015)
This study deals with marketing innovation, market orientation, and social capital in affecting the competitive advantage and marketing performance in Micro, Small, and Medium Enterprises (MSMEs) of embroidery in Central Java Province. In this respect, this study tried to test and analyze the effect of marketing innovation, market orienta-tion, and social capital on competitive advantage and marketing performance in Micro, Small, and Medium Enterprises (MSMEs) of embroidery in Central Java Province. The samples are 150 respondents as the owners of the embroidery business in Central Java Province. The technical analysis used is Structure Equations Modeling with AMOS Software version 22. The results show that: (1) marketing innovation has significant effect on competitive advantage; (2) market orientation has significant effect on competi-tive advantage; (3) social capital has significant effect on competitive advantage; (4) competitive advantage has significant effect on marketing performance; (5) marketing innovation has significant effect on marketing performance; (6) market orientation has significant effect on marketing performance; (7) social capital has no significant effect on marketing performance. The implication of this study is that the MSMEs of embroidery could improve marketing performance by increasing marketing innovation, market orientation, social capital and competitive advantage. This study also shows that competitive advantage is an intervening variable on marketing performance.